Fibre morphology, physical and chemical properties of Gliricidia sepium / Shaikh Abdul Karim Yamani Zakaria, Jamaludin Kasim and Nik Aziz Nik Mat - Zakaria, Shaikh Abdul Karim Yamani; Kasim, Jamaludin; Nik Mat, Nik Aziz (2004)
In this study, Gliricidia sepium of three age groups were produced and tested for their fibre morphology, physical and chemical properties. The methods used were accordingly to the TAPPI (1993) and Wise et. al (1946). Most of the properties studied increases with age except for fibre wall thickness that was approximately the same. The fibre was found to be unsuitable for papermaking due to its high fibre morphology and lignin values except for wood composite production.